2018
DOI: 10.1089/dna.2018.4222
|View full text |Cite
|
Sign up to set email alerts
|

ARG1Gene Polymorphisms and Their Association in Individuals with Essential Hypertension: A Case–Control Study

Abstract: The purpose of this study is to investigate the association of variant alleles (rs2781666 and rs2781667) at ARG1 to be involved in the generation of essential hypertension (EH) phenotypes in human subjects. The ARG1 noncoding polymorphisms (rs2781666; Chr6:131572419-G/T and rs2781667; Chr6:131573754-C/T) were investigated in 570 subjects, including 285 individuals diagnosed with EH. Determination of serum arginase activity and concentrations of nitric oxide catabolites were detected by the colorimetric enzymat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Approximately 95% of the cases are classed as essential hypertension (EH) (2)(3)(4); however, to date, the exact etiology and pathogenesis of EH have not been fully elucidated. Recent studies have found that the pathogenic factors of EH do not only involve the interaction between genetic and environmental factors (5,6), but are also correlated with human cytomegalovirus (HcMV) infection, microRNA (miRNA) regulation and inflammation activation, as well as other mechanisms (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 95% of the cases are classed as essential hypertension (EH) (2)(3)(4); however, to date, the exact etiology and pathogenesis of EH have not been fully elucidated. Recent studies have found that the pathogenic factors of EH do not only involve the interaction between genetic and environmental factors (5,6), but are also correlated with human cytomegalovirus (HcMV) infection, microRNA (miRNA) regulation and inflammation activation, as well as other mechanisms (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…We found, for example, ARG1, ARG2 and HGF. In a study by Shah S. F. A. et al, the authors suggested that a polymorphism in ARG1 may be linked to essential hypertension 44 . ARG1 is generally expressed in macrophages, coronary endothelial cells and vascular smooth muscle aortic cells, while ARG2 is expressed in human aortic endothelial cells and human umbilical vein endothelial cells 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Altered expression of SLC6A9 [56] and RHD (Rh blood group D antigen) [57], CHRFAM7A [58], ANXA3 [59], SLC1A5 [60], KCNH2 [61], HP (haptoglobin) [62], SELENBP1 [63], SNCA (synuclein alpha) [64], TGM2 [65], PINK1 [66], B2M [67], QPCT (glutaminyl-peptide cyclotransferase) [68], CBS (cystathionine beta-synthase) [69], NQO2 [70], GLRX5 [71], BASP1 [72], GAS7 [73], GPX1 [74], OLIG2 [75], RPTN (repetin) [76], IL33 [77], SOX10 [78], GRIK1 [79], ZFPM2 [80], SHANK3 [81], ERBB3 [82], ARC (activity regulated cytoskeleton associated protein) [83], GFAP (glial fibrillary acidic protein) [84], PLAT (plasminogen activator, tissue type) [85], GRIK5 [86], CACNB2 [87], NRXN2 [88], TERT (telomerase reverse transcriptase) [89], GNB3 [90], L1CAM [91], EGR3 [92], CAV1 [93], CACNA1B [94], MAGI1 [95], KIR2DL1 [96], PAH (phenylalanine hydroxylase) [97] and CYP3A5 [98] have been shown in schizophrenia. Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 [121], NFATC4 [122], TSLP (thymic stromal lymphopoietin) [123], WNT4 [124], MGP (matrix Gla protein) [125], FGFBP1 […”
Section: Discussionmentioning
confidence: 99%